Pengembangan Modul Pembelajaran Pengantin Paes Ageng Jangan Menir - Sri Irtawidjajanti; Lilis Jubaedah; Lintang Ayu Panjer Wengi; Zefanya Christy Gustanto (Journal on Education, 2024)
Yogya Paes Ageng Jangan Menir Bridal make-up is a type of make-up that requires its own technique in the manufacturing process, so students must be careful and follow the stages in completing it. The aim of this research is to develop a suitable learning media module, equipped with a video of the stages in the form of a QR barcode, which can be practically used by students or learners, as an independent learning media. The stages of the process of using cosmetics are in accordance with the times and the "proportional fit according to the shape of the face" technique. The research uses the Research and Development (R&D) method with a 4D development model, namely Define, Design, Develop and Disseminate. The data collection technique for this research is a questionnaire as a validation test assessment by material and media experts, as well as a practicality test by 5 small group students and 20 field group students. The results of this research show that the results of the 1st stage material expert validation test were 84% and 91% for the 2nd stage, the 1st stage media expert validation test was 82% and the 2nd stage was 91.1% with the category “very valid”. The results of the practicality test in the small group of 3 students were 91.6% and in the field test by 20 students it was 93.5% in the "very practical" category. The product assessment results of this learning module are feasible and practical for use as a learning medium.